IEEE Conference on Decision and Control and European Control Conference 2011
DOI: 10.1109/cdc.2011.6161176
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable navigation functions for unknown sphere worlds

Abstract: This paper introduces an algorithm for automatically tuning analytic navigation functions for sphere worlds. The tuning parameter must satisfy a lower bound to ensure collision avoidance and convergence. Until now analytic navigation functions have been manually tuned, although existence of a lower bound had been proved. A theoretical improvement on this lower bound is provided and the method is extended to unbounded manifolds. Then the required formulas are derived and algorithm described. So the lower bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…The form of NF proposed by Koditschek and Rimon (KRNF) require tuning of a parameter k ≥k min to guarantee the desired navigation properties. We extended KRNFs to unknown sphere worlds in [16] and the present work further extends them by proving thatk min exists for more general worlds.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The form of NF proposed by Koditschek and Rimon (KRNF) require tuning of a parameter k ≥k min to guarantee the desired navigation properties. We extended KRNFs to unknown sphere worlds in [16] and the present work further extends them by proving thatk min exists for more general worlds.…”
Section: Introductionmentioning
confidence: 85%
“…E-mail: jfilippidis@gmail.com, kkyria@mail.ntua.gr limited sensing range, non-holonomic systems [12] using dipolar NFs, incorporating prioritization [13] and multi-agent connectivity constraints [14], to partially known worlds by applying belt zones [15] and to unknown sphere worlds [16], as well as convex worlds using local diffeomorphisms [17]. Nonetheless, all of them involved either sphere worlds or diffeomorphisms, hence also simply connected obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…An algorithm for automatically tuning analytic navigation functions for sphere worlds was presented in [3]. The tuning parameter must satisfy a lower bound to ensure convergence to the desired value.…”
Section: Controller Designmentioning
confidence: 99%
“…Navigation functions are attractive solutions for path planning because of their relative ease of formulation, their packaging of various aspects of robot navigation into a single framework, and the fact that they prove convergence to the goal. Thus, they have attracted attention [4], [5], [6], [7] since they were first formulated. Some improvements have been made to the original approach.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [6] demonstrated that they work with moving obstacles in the workspace. Most recently, Filippidis [4] proposed an algorithm to automatically tune the navigation function gain. In their original formulation, navigation functions did not allow for incorporating an element of uncertainty which is inevitable to obstacles moving in practical environments.…”
Section: Introductionmentioning
confidence: 99%